Pelaksanaan Program Sekolah Ramah Anak di SMPN 1 Gunungsari - Dhea Anisya Pasha; Bagdawansyah Alqadri; Dahlan Dahlan; Mohammad Mustari (MANAZHIM, 2022)
This research aims to describe the implementation of the Child Friendly School Program (SRA), the supporting and inhibiting factors for the implementation of the SRA Program, as well as the benefits of implementing the SRA Program at SMPN 1 Gunungsari. The SRA program is a program that is expected to ensure the fulfillment of children's rights, such as getting protection to protect children from cases of violence that can occur in schools. This research used qualitative research with a phenomenological approach. Data collection techniques using observation techniques, interviews, and documentation. Based on the results of the study, it shows that the implementation of the SRA Program includes (1) SRA policies, (2) trained educators and education personnel of KHA and SRA, (3) implementation of child-friendly learning processes, (4) child-friendly facilities and infrastructure, (5) participation children, (6) the participation of parents, alumni, community organizations, and the business world, has not running optimally. This is because there are inhibiting factors in the form of the absence of a special SRA curriculum, funds that are still minimal, the absence of a special SRA team, and the participation of parents of students is still lacking. However, there are efforts in the form of supporting factors including the existence of human resources, infrastructure resources, and financial resources that can be optimized. In addition, there are benefits from implementing the SRA Program for schools, teachers, students, and the community.